Criteria of evaluation and territorial differentiation of geoecological conditions under the influence of the factor of technogenesis - Kalashnikava, Hanna I.; Yasoveev, Marat G. (Journal of the Belarusian State University. Ecology, 2019)
The study of the transformation of the natural environment under the conditions of anthropogenic impact is important for the sustainable development of the territory. The objects of medium-scale landscape mapping – natural territorial complex – in the ranks of the genera, subgenera and species are considered. The leading criteria for identifying the main ranks of natural and natural-anthropogenic landscapes are defined. The results of the geoecological analysis of the transformation of landscapes in areas with a high intensity of anthropogenic impact of the additional assessment category of geoecological conditions according to anthropogenic factors – «extremely unfavorable» are presented. It is shown that when identifying geo-ecological situations and developing measures for their improvement or prevention, the cartographic method of analysis makes it possible with a high degree of accuracy to convey the spatial features of the ecological situation, depending on the man-made transformations of the natural environment.